2005
DOI: 10.1289/ehp.7671
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned for the Study of Childhood Asthma from the Centers for Children’s Environmental Health and Disease Prevention Research

Abstract: The National Children’s Study will address, among other illnesses, the environmental causes of both incident asthma and exacerbations of asthma in children. Seven of the Centers for Children’s Environmental Health and Disease Prevention Research (Children’s Centers), funded by the National Institute of Environmental Health Sciences and the U.S. Environmental Protection Agency, conducted studies relating to asthma. The design of these studies was diverse and included cohorts, longitudinal studies of older child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…An intense effort was made to maintain contact and involvement with enrolled families. Retention rates and degree of data missingness are similar to other reports in the literature (Eggleston et al, 2005; Mortimer et al, 2002). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An intense effort was made to maintain contact and involvement with enrolled families. Retention rates and degree of data missingness are similar to other reports in the literature (Eggleston et al, 2005; Mortimer et al, 2002). …”
Section: Discussionsupporting
confidence: 87%
“…Although many challenges with recruitment and retention exist for a study of this length and intensity (Eggleston et al, 2005), the CBPR approach and guidance from our community partners was instrumental in addressing these challenges in a city where many families struggle with financial and social stressors. An intense effort was made to maintain contact and involvement with enrolled families.…”
Section: Discussionmentioning
confidence: 99%
“…In two countries the information on the analytical results that all participants received served as the only incentive. But as Eggleston et al (2005) reported, this is not negative: Sometimes information provided to the participants attracted them most to the study, more than other offered incentives. Theses authors also described that reimbursements for electricity costs during the survey (up to US $200) or reimbursements for travel expenses are common.…”
Section: Discussionmentioning
confidence: 99%
“…The CHSA-C was adapted from an existing parent report instrument, the Children's Health Survey for Asthma (CHSA); the strong validity and reliability of the CHSA were reported previously, 28 and the instrument has been used in numerous asthma studies. [29][30][31][32] We conducted intensive oneon-one interviews with young children before data collection, to make practical, child-friendly, questionnaire modifications (such as a calendar review to facilitate understanding of a 2-week recall period and visual representation of Likert-type response choices). Details about the CHSA, the development of the CHSA-C, and the data collection process are available from the authors at the American Academy of Pediatrics.…”
Section: Overall Study Designmentioning
confidence: 99%